An evaluation of the relevance of the UP School of Library and Information Studies' (SLIS) Master of Library and Information Science (MLIS) program through its graduates' perception - Racines, Christian Q. (2016)
The Master of Library and Information Science (MLIS) program had been offered by the UP School of Library and Information Studies (SLIS) since 1962. Since then, it has produced a number of graduates that has excelled in the field of library and information science.